2014
DOI: 10.1364/boe.5.000848
|View full text |Cite
|
Sign up to set email alerts
|

Detection of swelling of single isolated mitochondrion with optical microscopy

Abstract: Volume regulation under osmotic loading is one of the most fundamental functions in cells and organelles. However, the effective method to detect volume changes of a single organelle has not been developed. Here, we present a novel technique for detecting volume changes of a single isolated mitochondrion in aqueous solution based on the transmittance of the light through the mitochondrion. We found that 70% and 21% of mitochondria swelled upon addition of a hypotonic solution and Ca 2+, respectively. These res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
(15 reference statements)
2
7
0
Order By: Relevance
“…The obtained mitochondria were suspended in suspension buffer [10 mM Tris-HCl, 250 mM sucrose, 0.5 mM EGTA, (pH 7.4)]. Each preparation was assayed for ATP production [24] upon addition of 5 mM Namalate, giving a rate of 329 ± 34 nmol ATP/mg of protein/min (mean ± SE, n = 3), which was comparable to values reported previously [19] and which showed that mitochondria used for the experiments had a high potential for ATP production. Protein content was determined using a BCA protein assay with BSA as a standard.…”
Section: Preparation Of Isolated Mitochondriasupporting
confidence: 81%
See 1 more Smart Citation
“…The obtained mitochondria were suspended in suspension buffer [10 mM Tris-HCl, 250 mM sucrose, 0.5 mM EGTA, (pH 7.4)]. Each preparation was assayed for ATP production [24] upon addition of 5 mM Namalate, giving a rate of 329 ± 34 nmol ATP/mg of protein/min (mean ± SE, n = 3), which was comparable to values reported previously [19] and which showed that mitochondria used for the experiments had a high potential for ATP production. Protein content was determined using a BCA protein assay with BSA as a standard.…”
Section: Preparation Of Isolated Mitochondriasupporting
confidence: 81%
“…DIC images and transmitted light images of individual mitochondria and beads were acquired with an inverted microscope (IX70, Olympus, Tokyo, Japan) equipped with a 20 × objective (UPlanSApo, Olympus), a 2 × relay lens (U-TVCAC, Olympus) and a cooled CCD camera (6.45 μm/pixel at 1x) (Sensicam QE, PCO AG; Kelheim, Germany). The wavelength used for the measurements was selected with a 10-nm bandpass filter centered at 546 nm [19], because the effects of redox changes of mitochondrial proteins on the absorption of mitochondrial suspensions are small within this range of the wavelength. To modulate the phase difference between beam a and beam b in Fig.…”
Section: Differential Interference Contrast (Dic) Imagingmentioning
confidence: 99%
“…The current values seen in these experiments are consistent with very few pores, but further experiments will be needed to confirm this interpretation. Further, very recent imaging data measuring single mitochondrial swelling under conditions similar to those presented in this work demonstrated that swelling occurs in a steplike manner, suggesting that it is induced by the activation of a relatively small number of pores ( Morikawa et al, 2014 ; Shibata et al, 2019 ). Interestingly, this study reported that despite the fact that all mitochondria undergo depolarization indicating PT activation, not all of them swell, suggesting an intriguing possibility that the high-conductance mode of PTP is not activated in every mitochondrion.…”
Section: Discussionsupporting
confidence: 64%
“…The cells were further incubated at 25°C for 50 min, and 50-l aliquots of the sample were held between a slide glass and a coverslip and placed on the stage of an inverted optical microscope (IX-70; Olympus; Tokyo, Japan) equipped with a 40ϫ objective lens (Uapo40ϫ/340, NA ϭ 0.9; Olympus) (19). Ten minutes after placement, images were photographed with a cooled CCD camera (Sensicam QE, PCO AG, Kelheim, Germany) every 2 s, and 300 images were collected over 10 min.…”
Section: Measurement Of D-ala-d-alamentioning
confidence: 99%